2020
DOI: 10.12681/mms.21927
|View full text |Cite
|
Sign up to set email alerts
|

First records of non-indigenous species in port of Arzew (Algeria: southwestern Mediterranean)

Abstract: Maritime transport is considered to be one of the main factors to transfer non-indigenous species (NIS), through biofouling of ships’ hulls and ballast water. Therefore, ports and marinas constitute hot spots for the introduction of species carried by international shipping and therefore are important sites for initiating biological monitoring. In this study, the port of Arzew (Algeria, Southern Mediterranean) was surveyed for the presence of NIS and cryptogenic species. The fouling communities of floating sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The implementation of environmental parameters in this study, as well as the shipping routes linking the ecoregions to the port of Arzew, allowed us to analyze on average the capacity of species to resist the stress generated by the voyage and their ability to adapt. The results are in line with Zenetos studies on the Mediterranean Sea (Zenetos et al, 2012), and with observations by (Grimes et al, 2018) and (Bensari et al, 2020) and other reports of introductions into the Mediterranean Sea. At the end of this study, we can suggest the introduction of speci c regulations on the re t of the two categories of ships: OIL/CHEMICAL TANKER and LPG TANKER.…”
Section: Discussionsupporting
confidence: 93%
“…The implementation of environmental parameters in this study, as well as the shipping routes linking the ecoregions to the port of Arzew, allowed us to analyze on average the capacity of species to resist the stress generated by the voyage and their ability to adapt. The results are in line with Zenetos studies on the Mediterranean Sea (Zenetos et al, 2012), and with observations by (Grimes et al, 2018) and (Bensari et al, 2020) and other reports of introductions into the Mediterranean Sea. At the end of this study, we can suggest the introduction of speci c regulations on the re t of the two categories of ships: OIL/CHEMICAL TANKER and LPG TANKER.…”
Section: Discussionsupporting
confidence: 93%
“…A significant number of NIS are found on the Algerian coast (106 species) (Bakalem unpublished data), including two Crustaceans Peracarida (Elasmopus pectenicrus and Eocuma sarsii) [4,116]. Recently, Bensari et al [117] identified two new NIS Peracarida: the Tanaidacea Zeuxo coralensis Sieg, 1980 (12 individuals) and the Isopoda Paracerceis sculpta (Holmes, 1904) (419 individuals) in the harbour of Arzew, species observed on the hulls of fishing ship and on a tyre-buoy; these authors attributed an established status to these species.…”
Section: Non-indigenous Species (Nis)mentioning
confidence: 99%